Imperfect Competition in Selection Markets - Mahoney, Neale; Weyl, E. Glen (The Review of Economics and Statistics, 2017)
Policies to correct market power and selection can be misguided when these forces coexist. We build a model of symmetric imperfect competition in selection markets that parameterizes the degree of market power and selection. We use graphical price-theoretic reasoning to characterize the interaction between these forces. Using a calibrated model of health insurance, we show that the risk adjustment commonly used to offset adverse selection can reduce coverage and social surplus. Conversely, in a calibrated model of subprime auto lending, realistic levels of competition can generate an oversupply of credit, implying that greater market power is desirable.